Assessing Urban Renewal Sites in Lahore - Ali, Rashid; Waqar, Zeenat; Ahmad, Muhammad; Rehan Sharif, Muhammad (Journal of World Science, 2022)
Introduction: Cities try to adapt to the rapidly changing global trends by updating themselves. In Pakistani cities, particularly in the last decade, the practices, processes, and consequences of urban renewal have sparked some debate. The 'new' space acquired or converted in the city is also significant in terms of its impact on urban identity. In this context, this research study aims to identify the effects of urban renewal in various parts of the world, especially in Lahore, Pakistan. Method: This study collects and analyzes quantitative and qualitative data. A method that relies on GIS-based urban renewal site identification. Result: Economic development in Lahore is not carried out well as almost 52% is dominated by old buildings, 28% of the roads at the Renewal location are in an abandoned condition, the quality of drinking water is low, and the inspection of garbage on the streets that is not paid attention to illustrates that there is no solid waste management system the good one. Conclusion: The development of Lahore's renewal was not carried out properly because 60% of the people lived in the Renewal site. The legacy of 27% of the local population was not interested in regional development, so urban renewal tended to be ignored.